Development of melon-flavored and-colored peanut beverage - Vendiola, Nancy Querubin; Azanza, Ma. Patricia V. (1997.)
The general objective of the study was to develop an acceptable melon-flavored and -colored peanut beverage. The study was divided into three phases. The first phase involved the preparation of the peanut beverage using the Modified Illinois Process by Rubico et al. (1989). This beverage was incorporated with different concentrations of melon flavor and orange color to determine the most acceptable formulation. Sensory evaluations and analyses of data found that the most acceptable formulation of peanut beverage was with the 0.70% melon flavor and 7.5 R 7/6 simulated orange food color incorporations. The beverage had a medium peach color that was liked slightly. The melon odor was described to be ideal in strength but was neither liked nor disliked. Melon, peanut, and beany flavors of the test beverage were all found to be slightly weak that were rated neither like nor disliked. The overall acceptability rating of the peanut beverage was liked slightly. The second phase involved storage stability studies of the beverage packaged in high-density polyethylene plastic bottles and stored at 5°C in a walk-in chiller. Freshly prepared beverage at 0 day of storage had Total Plate Count (TPC), Yeast and Mold Count (YMC), A. flavus/parasiticus Count (AFPC), pH, % soluble solids and color values of 2.3 x 10^4 cfu/ml, 1.0 x 10^1 cfu/ml, <10^2 cfu/ml, 6.73, 10.97°Bx, and 7.5 R 7/6, respectively. Storage was terminated with the coagulation of the beverage on the 9th day with TPC, YMC, AFPC, pH, % soluble solids and color having values of 3.0 x 10^5 cfu/ml, <4.7 x 10^2 cfu/ml, <10^2 cfu/ml, 5.33, 10.97°Bx and 7.5 R 7/6, respectively. The third phase involved the cost analysis of the beverage. The cost of producing the melon-flavored and -colored peanut beverage with an additional 10% mark-up amounted to 5.94 (Php) for every 250 ml bottle. Compared with the retail price of 13.50 (Php) by Magnolia- Nestle's Pasteurized Melon Milk, the melon flavored and colored peanut beverage was cheaper by 56%. Recommendations for the melon flavored and colored peanut beverage included heating he beverage during homogenization, addition of stabilizers and more hygienic bottling procedures to prolong the beverage's shelf life.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Beverages